Lispocephala Pokorny 1893 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Lispocephala Pokorny, 1893 Lispocephala Pokorny, 1893: 532. Type-species: Anthomyia alma Meigen, 1826, by original designation. Lispocephala alma (Meigen, 1826) Anthomyia alma Meigen, 1826: 188. Type-locality: not stated (probably Austria, Vienna). Holotype ♀, not located and presumed destroyed (Pont, 1986b: 211). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92). General distribution: Holarctic Region; in the Palaearctic, from Europe east to China. Lispocephala erythrocera (Robineau-Desvoidy, 1830) Caricea erythrocera Robineau-Desvoidy, 1830: 534. Type-localities: France, Saint-Sauveur and Paris. Syntypes, formerly in Robineau-Desvoidy collection, now destroyed (not MNHN). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92); Yamalo-Nenetskiy AO: Salekhard [as “Tobol’ skaya Guberniya, Obdorsk" in German], and Respublika Sakha: Amginskiy Ulus [as “Yakutsk (Amgin)” in German] (Hennig, 1961a: 485); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 230); West and East Siberia (Pont, 1986a: 194). General distribution: Holarctic Region; in the Palaearctic, from Europe east to Japan. Lispocephala pallipalpis (Zetterstedt, 1845) Anthomyza pallipalpis Zetterstedt, 1845: 1678. Type-locality: Sweden, Lule Lappmark, Luleå. Lectotype ♂, MZLU (designated by Collin, 1963: 283; Pont, in press). Siberian records: Kurganskaya Oblast’ (Sorokina, 2006a: 230). General distribution: Holarctic Region; in the Palaearctic, from Europe, Russia (West Siberia), Japan; USA (New Hampshire). Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on pages 70-71, DOI:10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926